The Impact of Microfinance on the Income of Micro, Small, and Medium Enterprises (MSE) in Indonesia: A Sectoral Analysis - Wirawan, Rendra (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This study investigates the impact of various types of microfinance on the income of micro, small, and medium enterprises (MSMEs) in Indonesia. Utilizing data from the 2022 Micro and Small Industry Survey conducted by Statistics Indonesia, the research employs multiple linear regression analysis to assess the effects of cooperative loans, non-bank financial institutions, and People's Business Credit (KUR) on MSME income across different industry sectors. The results reveal that KUR significantly enhances income across various sectors, demonstrating its effectiveness in improving financial performance. In contrast, the impact of cooperative loans and non-bank financial institutions varies by sector, with cooperative loans showing significant effects only in the tobacco processing industry and non-bank financial institutions impacting primarily the textile sector. These findings highlight the importance of selecting appropriate microfinance options tailored to sector-specific needs. The study underscores that strategic microfinance choices can significantly boost MSME competitiveness and operational efficiency in Indonesia.